Threats and conservation status of Common and Roseate terns Sterna hirundo/S. dougallii in the Azores : A case study for Terceira Island - Lamelas-López, Lucas (2022)
The Azores Archipelago holds the second most important population of Roseate Terns in the North Atlantic. However, the size of the population has been decreasing. In this study, we used remote-sensing cameras and visits to the main colonies of Common Terns Sterna hirundo and Roseate Terns S. dougallii on Terceira Island to identify the causes of breeding failure. Nest depredation by introduced mammals, particularly rats and cats, was the main cause of breeding failure, leading, in some cases, to the complete destruction of the colony. Additional threats included nest disturbance by humans and dogs, which caused the destruction of some nests. Measures aimed at mitigating depredation were tested but in the case of rodents, control plans proved difficult to achieve. This is probably because rodents are widespread in the Azores, they are not limited by food resources, and/or trapping methods are ineffective.